THE EFFECTIVENESS OF THE IMPLEMENTATION OF CRITICAL DISCOURSE ANALYSIS INSURANCE ADVERTISING IN ARGUMENTATIVE WRITING LEARNING FOR UNIVERSITY STUDENTS - Rusdhianti Wuryaningrum (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to describe the application through the Fairclough Critical Discourse Analysis (CDA) model on insurance advertising and its effectiveness in argumentative writing learning. The research method is a mixing qualitative and quantitative. Qualitative methods are applied by using the Fairclough's CDA model that applies micro, meso, and macro dimensions. Quantitative methods are used to measure the effectiveness of Fairclough CDA modelon argumentative writing learning. The results showed the use of language, connectivity, and hegemony with future concerns caused by lifestyle and social demands, and calamity with phrases as a form of the claim that needs to be made a counterclaim. This strongly supports the argumentation content.  The Mann Whitney U test shows significance value of 0,000 is ≤0.005. Thus, it can be concluded that Fairclough CDA modelapplication of learning with CDA is effective for improving learning outcomes in argumentative writing.